2017
DOI: 10.1182/blood-2017-02-764787
|View full text |Cite
|
Sign up to set email alerts
|

Strict tropism for CD71+/CD234+ human reticulocytes limits the zoonotic potential of Plasmodium cynomolgi

Abstract: Key Points• Zoonotic P cynomolgi switches red cell tropism for reticulocytes expressing Trf1 (CD71 1 ) and DARC (CD234 1 ). • In the human host, P cynomolgi displays an almost identical rheopathobiology to P vivax.Two malaria parasites of Southeast Asian macaques, Plasmodium knowlesi and P cynomolgi, can infect humans experimentally. In Malaysia, where both species are common, zoonotic knowlesi malaria has recently become dominant, and cases are recorded throughout the region. By contrast, to date, only a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Only one case of a human naturally infected with P. cynomolgi has been reported, which was in Peninsular Malaysia [ 30 ], while no natural human infection by P. inui has been reported. Human infections by P. cynomolgi could be limited by its requirement for select receptors on human RBCs [ 45 ]. Lack of suitable vectors could also affect invasion of human RBCs by these species.…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of a human naturally infected with P. cynomolgi has been reported, which was in Peninsular Malaysia [ 30 ], while no natural human infection by P. inui has been reported. Human infections by P. cynomolgi could be limited by its requirement for select receptors on human RBCs [ 45 ]. Lack of suitable vectors could also affect invasion of human RBCs by these species.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium cynomolgi is a closely related zoonotic macaque parasite that has recently been isolated from human hosts [49]. Like P. knowlesi, P. cynomolgi invades macaque erythrocytes indiscriminately, but is reticulocyte-restricted in human blood, potentially limiting its zoonotic potential [50]. Kosaisavee et al .…”
Section: Monkey In the Middle: The Emerging Public Health Threat Posementioning
confidence: 99%
“…Kosaisavee et al . [50] revealed that this phenotype is attributable to the reliance of this parasite upon transferrin receptor 1 and the Duffy antigen/receptor for chemokines (DARC) during human erythrocyte invasion. Long-term in vitro culture of P. cynomolgi in human blood and comparison with P. knowlesi may reveal convergent mechanisms of adaptation to the human host and offer novel insight into process of zoonotic emergence.…”
Section: Monkey In the Middle: The Emerging Public Health Threat Posementioning
confidence: 99%
“…On the basis of the results, the Fy b-long -expressing K562 erytholeukemia cell line was selected for differentiation and enucleation studies. Although permissivity for these P. vivax-type parasites may not be definitive proof that the cells are also P. vivax permissive, P. knowlesi and P. cynomolgi were chosen based on the fact that they are good models for the Fy receptor-dependent invasion of red cells [20,21], where P. cynomolgi, in particular, is the parasite phylogenetically and biologically most closely related to P. vivax.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that P. vivax [19] and its closely related non-human primate malarias P. knowlesi [20] and P. cynomolgi [21] require the Duffy blood group antigen receptor to invade their host red blood cells. However, the K562 erythroleukemia cell line does not express this antigen.…”
Section: Generation Of Fy Receptor-expressing K562 Cell Linesmentioning
confidence: 99%